Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Using recent genetic history to inform conservation options of two Lesser Caymans iguana (Cyclura nubila caymanensis) populations - Thea F. Rogers; Ewan H. Stenhouse; Hannah Wilson; Morgan Pendaries; Michael W. Bruford; Matthias Goetz; Pablo Orozco-terWengel (Conservation Genetics, 2024)
The Sister Islands rock iguana ( Cyclura nubila caymanensis ) is critically endangered and endemic to the Caribbean islands Little Cayman and Cayman Brac. The Cayman Brac population and indeed the entire species is under threat from habitat destruction, invasive species, and anthropogenic impacts on the island. We assessed the genetic diversity, estimated effective population sizes, and tested for differentiation of populations between these two islands to inform potential future translocation should this be needed for the Cayman Brac population. Two mitochondrial DNA markers (cytochrome b and NADH subunit 4) and seven DNA microsatellite markers were used to assess the genetic diversity, genetic structure, demographic history, and effective population size of the two iguana populations. Mitochondrial DNA showed no genetic differentiation between populations; however, we found little to moderate divergence with microsatellites. We compared multiple demographic scenarios and revealed that ongoing gene flow is likely. The demographic history implied a significant genetic bottleneck around 10,000 years ago, coinciding with the sea level rise at the close of the last glacial period, and the start of the Holocene. Estimates of current effective population sizes indicate a small-scale number of breeders on each island of similar magnitude to the census mature population size (between 100 and 800 individuals). The relatively low differentiation between populations supports the possible development of active genetic management plans to manage the declining populations of the Sister Islands rock iguana.

CRISPR/Cas-mediated plant genome editing: outstanding challenges a decade after implementation - Teodoro Cardi; Jana Murovec; Allah Bakhsh; Justyna Boniecka; Tobias Bruegmann; Simon E. Bull; Tom Eeckhaut; Matthias Fladung; Vladislava Galovic; Anna Linkiewicz; Tjaša Lukan; Isabel Mafra; et al. (Trends in Plant Science, 2023)

Increasing zoo’s conservation potential through understanding barriers to holding globally threatened amphibians - Leana Brady; Richard P. Young; Matthias Goetz; Jeff Dawson (Biodiversity and Conservation, 2017)